The Pottery Technology From Bukit Tengkorak,A 3000-5000 Year Old Site In Borneo, Malaysia. - Vandiver, Pamela; Chia, Assoc Prof. Dr. Stephen, Ming Soon (Materials Research Society, 1997)
Bukit Tengkorak (Scull Hill) is a Neolithic period rock shelter complex and prehistoric pottery production site in southeastern Sabah, about 5 miles southwest of Semporna in Borneo, Malaysia at GPS N 4 7 20.08 and E 118 37 04.3. It was excavated for a 5-week season in 1995 and another in 1994 by a joint University of Science and Sabah Museum team under the direction of S. Chia.